PERENCANAAN MUSEUM KAPAL MOTOR DI TENGGARONG DENGAN PENDEKATAN ARSITEKTUR TROPIS - Arif, Mustafa; Prasetyo, - (Jurnal Totem : Architecture, Environment, Region and Local Wisdom, 2020)
Tenggarong City has Mahakam River that connects between West Kutai Regency to Samarinda. The river length reaches 920 kilometers.Â  This will be planning the Motor ship Museum, at the stage of this research in the form of primary and secondary data collection methods, analysis method consists of the analysis of the needs of space, space, space relations, site, building basic coefficients and Green basic coefficients, space and musical arrangement space, mass and mass material, shape, structure, utilities. Concept of building with the emphasis of tropical architecture in the application of building lighting Museum.Total amount of space 6,341.7 m2 divided by the area of building basic coefficient 6,341.7 area of the green base coefficient 4,227.8, for analysis site on the research is reviewing such as drainage, wind direction, Sun. Utility analysis such as clean water, dirty, rainy and piping on the Museum area. Type of vessel in the show, namely, motor ship freight, mines, vehicle transportation with the concept of cluster in the form of mass arrangement on the site, the transformation of the ship resembles the Mahakam river water bus transport ship, and the history of the ship. Â Keywords: Museum, Motor ship, Tenggarong City